Language, Identity, and Quarter-Life Crisis: A Systemic Functional Linguistics Perspective on Indonesian Emerging Adults in Educational Contexts: Penelitian - Andi Sahtiani Jahrir (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study analyzes how young Indonesian adults express their quarter-life crisis (QLC) experiences in an educational context using a Systemic Functional Linguistics (SFL) approach. The aim is to demonstrate that QLC is not only psychological in nature, but also manifests as linguistic performances of identity, insecurity, and resilience. The method used is mixed, combining descriptive statistics and discourse analysis. Data were collected from 33 respondents aged 18–30 years in Makassar through a 17-item Likert questionnaire covering insecurity, future anxiety, motivation, social comparison, religiosity, and satisfaction. Quantitative analysis was conducted by calculating frequencies, while responses were reanalyzed using the SFL Assessment framework (Attitude, Engagement, Graduation). The results reveal three main themes: (1) high anxiety, 36.4% always worry about the future and 54.5% sometimes feel insecure; (2) relational difficulties, 66.7% have difficulty trusting others and 21.2% often compare themselves on social media; (3) religiosity as a dominant coping strategy, 72.7% rely on faith in God's help. Linguistically, this pattern appears as negative affect, negative judgments of others, and positive faith-based modalities.